Metabolismo comparado de jardins de fungo de formigas Attini - Somera, Alexandre Favarin [UNESP] (2014)
Attine ants build nests containing microbial cultures named fungus gardens to deal with the environment.The cultivation, or agriculture, is divided into three major phylogenetic groups: lower, with hundreds of individuals; higher with thousands of individuals; and the higher subgroup of leafcutters with millions of individuals. The demography of nests and ant survival depend on the ability of the microbiota in providing nutrients to the nest from materials foraged by ants. This work comparatively studied the functional characteristics of 342 fungus gardens from 8 species of ants representing these three major groups. A holistic strategy was applied to deal with these issues. Each system was generalized in compartments connected by vectors of flows and studied according to a black box approach using respirometric, enzymological and spectroscopic techniques to characterize substrates, hydrolysis products, enzymatic activity and biokinetics of each fungus garden. The evaluation of the substrate indicated replacement of high recalcitrant litter materials used in the lower group by less recalcitrant materials in higher group and fresh vegetation rich in easily degradable products in leaf-cutters. This change correlated positively with the exchange of a general enzyme system observed in the lower group to a more powerful and specialized enzyme system directed to the degradation of starch and hemicellulose in higher and leaf-cutters groups. Accumulation rates of xylose exceeded glucose only in leaf-cutters indicating preference for hemicelluloses. The physiological profile of the microbiota follows the modifications related to the product generated, starting from a lower generalist system to a leaf-cutter specialist in xylose. Thus, the physiological consequences of enzyme specialization observed in higher systems appeared only inleaf-cutters. This result is linked to the use of fresh substrate rich in hemicelluloses. The changes were accompanied...